2001
DOI: 10.1243/0954411011533698
|View full text |Cite
|
Sign up to set email alerts
|

Effect of contact stress on friction and wear of ultra-high molecular weight polyethylene in total hip replacement

Abstract: This paper studies the effect of contact stress on friction and wear of ultra-high molecular weight polyethylene (UHMWPE) acetabular cups by means of friction and wear joint simulator testing under serum lubrication. For a given applied load, increasing the contact stress by increasing the ball/socket radial clearance decreased both the coefficient of friction and the wear rate. Friction and wear were highly correlated. The dependence of friction on contact stress for the UHMWPE socket under serum lubrication … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
80
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(89 citation statements)
references
References 15 publications
9
80
0
Order By: Relevance
“…The lower wear depths between the two maximum depth locations were due to the reduced crossshear motions which led to reduced wear coefficients. The computationally predicted effect of bearing clearances on wear is compared with the experimental measurement of a simulator test by Wang et al 10 for a 32 mm diameter bearing with varied radial clearances, as shown in Figure 6. The larger contact area corresponds to smaller clearance since the contact area increases when the clearance decreases.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The lower wear depths between the two maximum depth locations were due to the reduced crossshear motions which led to reduced wear coefficients. The computationally predicted effect of bearing clearances on wear is compared with the experimental measurement of a simulator test by Wang et al 10 for a 32 mm diameter bearing with varied radial clearances, as shown in Figure 6. The larger contact area corresponds to smaller clearance since the contact area increases when the clearance decreases.…”
Section: Resultsmentioning
confidence: 99%
“…This has also been demonstrated in a laboratory simulator study. 10 However, that experimental study attributed the effect of the clearance on wear to increased pressure and lack of lubrication rather than contact area. The role of the clearance in the design has not been fully investigated, and the quantitative understanding of its effect may provide better design options with improved wear performance.…”
Section: Introductionmentioning
confidence: 97%
“…5, 6) which showed a fourfold reduction in wear rate compared to knees with a curved insert. The effect of contact pressure on wear has been previously reported for unidirectional motion pin-on-plate studies [2] and the effect of conformity on surface area on wear has also been reported in the hip [26]. This approach to reducing surface wear by reducing conformity and wear area contradicts the thinking of the 1980s and 1990s [5,6,8,19] that led to more conforming designs in order to avoid the risk of delamination and fatigue following oxidative degradation.…”
Section: Discussionmentioning
confidence: 98%
“…In [5], the polymer wear in terms of cumulative linear and volume wear when the wear factor is chosen to be a function of contact pressure was first evaluated. Herewith, various known wear factor dependencies on the contact pressure were investigated as contained in [9,10,11]. Since the contact pressure in the above formulae is a power function with a negative degree, these relations give a decrease in wear factor depending on the increase of a contact pressure, which means a reduction of wear values that are not uniquely consistent with the physics of the process.…”
Section: Introductionmentioning
confidence: 99%